A Systematic Review of YouTube for English Language Teaching - Ainun Jariyah; Aeni Hidayati; Nafan Tarihoran (PT. Intelek Cendikiawan Nusantara, 2025)
YouTube has emerged as one of the most widely used digital platforms in English Language Teaching (ELT), offering a range of benefits for language acquisition, engagement, and content accessibility. This systematic review aims to analyze existing literature on the role of YouTube in ELT, highlighting its effectiveness, challenges, and pedagogy. The review follows a systematic methodology, selecting relevant studies from reputable academic databases. Findings indicate that YouTube enhances language exposure, supports multimodal learning, and fosters autonomous learning. However, content reliability, distraction, and digital literacy must be addressed. This study contributes to a better understanding of YouTube's role in ELT and provides recommendations for its effective integration in the classroom.